2009
DOI: 10.1097/eja.0b013e32832a0c7c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clonidine and midazolam premedication on bispectral index and recovery after elective surgery

Abstract: Clonidine augmented haemodynamic stability and partially blunted stress responses as determined by adrenocorticotropic hormone plasma levels. In addition, clonidine did not delay postoperative recovery. Therefore, surrogate parameters indicate that preanaesthetic medication with clonidine may be superior to midazolam in healthy individuals. Further studies have to confirm these results with regard to outcome parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
3
15
1
2
Order By: Relevance
“…Our result was similar to that of Paris, Andrea et al, (2009) [28] who concluded that Clonidine (150 g orally), but not midazolam (7.5 mg orally), augmented hemodynamic stability and partially blunted stress responses as determined by plasma adrenocorticotropic hormone (ACTH) levels.…”
Section: Discussionsupporting
confidence: 92%
“…Our result was similar to that of Paris, Andrea et al, (2009) [28] who concluded that Clonidine (150 g orally), but not midazolam (7.5 mg orally), augmented hemodynamic stability and partially blunted stress responses as determined by plasma adrenocorticotropic hormone (ACTH) levels.…”
Section: Discussionsupporting
confidence: 92%
“…3); deshalb konnten, wie in der Studie von Paris et al [25], aber im Gegensatz zu dem STAI-Testergebnis, keine Gruppenunterschiede festgestellt werden. Zudem war die Dosierung in der Untersuchung von Paris et al [25] weder alters-noch gewichtskorrigiert: Midazolam 7,5 mg p.o. und Clonidin 150 μg p.o.…”
Section: Clonidinunclassified
“…Although used mainly during surgery or for sedation in intensive care unit, only few studies have evaluated the role of 2-agonist as premedication to reduce preoperative anxiety [44,53,54]. While a decrease of preoperative anxiety was observed by Aanta et al [44] and Carabine et al [55], in a recent study by Paris et al [41], clonidine (150 g orally 60-90 minutes before surgery) was able to attenuate the stress response, improve hemodynamic stability, but not to decrease preoperative anxiety [41]. Moreover, higher doses of clonidine (300 g orally) are associated with potential hemodynamic side effects such as hypothesion that, because of the long half-life of this medication, may occur and persist also during the postoperative period [55,56].…”
Section: Alpha2-agoinstsmentioning
confidence: 99%
“…Central nervous system effects are dose depended but do not cause respiratory depression such as benzodiazepines [17,[38][39][40]. It has been shown that premedication with 2-agonists blunt the stress response during laringoscopy, improve homodynamic stability, decrease postoperative pain, shivering, have an anesthetic and opioid sparing effect, reduce intraoperative blood loss and postoperative nausea and vomiting (PONV) and ileus [37,[41][42][43][44][45][46][47]. Furthermore, premedication with 2-agonists has shown to improve glycemic control [48] and decrease protein breakdown after surgery [49].…”
Section: Alpha2-agoinstsmentioning
confidence: 99%